Thermal behavior of apatite-like compounds Pb₁₀(ХO₄)₆(OH)₂, where X = P, V - Smolyak Svitlana (DataverseUA, 2025)
A comprehensive study of the thermal stability of apatite-like compounds Pb₁₀(ХO₄)₆(OH)₂, where X = P, V, was conducted. Differential thermal analysis (DTA), thermogravimetry (TG) and differential thermogravimetry (DTG) were used for this purpose. The use of these methods allowed us to determine the temperature ranges of stability, the nature of thermochemical transformations, as well as mass losses associated with dehydration, decomposition and phase transitions.